2020
DOI: 10.1088/1361-6668/aba79d
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the plastic deformation of coated conductors deconstructed from ultra-high field test coils

Abstract: REBCO coated conductors are now being used for building very high-field magnets with large electromagnetic stresses, both expected ones due to transport current ⃗ J × ⃗ B stresses and additional stresses resulting from the large screening currents inherent in wide tapes. Post mortem analyses of several recent test coils operated above 40 T show that significant conductor plastic deformation occurs, even for JBR stresses well below the ∼1 GPa yield of the Hastelloy substrate of the conductor. To investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…As mentioned above, the middle SP coils (#3-#10) are mechanically damaged because of a large induced current, in the case A. Meanwhile, it was reported that the top and bottom SP coils were probably damaged due to a screening current [22]. As illustrated in Fig.…”
Section: B Cause Of Small Strain On Sp #2 In Case Amentioning
confidence: 85%
“…As mentioned above, the middle SP coils (#3-#10) are mechanically damaged because of a large induced current, in the case A. Meanwhile, it was reported that the top and bottom SP coils were probably damaged due to a screening current [22]. As illustrated in Fig.…”
Section: B Cause Of Small Strain On Sp #2 In Case Amentioning
confidence: 85%
“…Meanwhile, the screening current (SC) induced in the REBCO CCs generates an undesired magnetic field [12,13,14,15]. Recently, it was pointed out that the screening current may substantially enhance magnetic stress in REBCO magnets [16,17,18,19,20,21]. To estimate the peak stress accurately, the importance of the accurate computation of the screening current distribution must be enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…On 2017, a world-record high DC magnetic field of 45.5 T was generated with insert no-insulation (NI) Rare-Earth Barium Copper Oxide (REBCO) pancake coils (14.4 T), called "LBC3", and an outsert resistive magnet (31.1 T) [5]. After 45.5-T generation, the insert NI REBCO pancake coils were quenched, and plastic deformations of REBCO tapes were observed [6]. Since the Hastelloy substrate of REBCO tapes is stiff, whose yield point is 800 MPa [7], REBCO tapes have great mechanical properties together with high critical current density and critical magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…aged in several cases after high field generation; e.g., the LBC3 [5], [6], and the MIT 1.3-GHz NMR insert magnet [8].…”
Section: Introductionmentioning
confidence: 99%